Spatial-temporal variation of the ecosystem services value (ESV) in the Yellow River Delta wetland and its response to land use/land cover changes (lu/lc) - Xiaoshuang Fu; Yang Yang; Xianqi Zhang (Journal of Freshwater Ecology)
The assessment of wetland ecosystem services value can provide theoretical basis for regional social and economic development, ecological environment protection and other planning and measures. Based on the factors of hydrology, meteorology, society, economy, resources, environment and culture, the value of wetland ecosystem services in the Yellow River Delta was evaluated by the revised equivalent factor method. The results showed that from 2005 to 2020, the area of tidal flat wetland decreased by 54.35%, and aquaculture increased by 206.91%. The total value of wetland ecosystem services increased from 28.03 billion CNY to 35.77 billion CNY, an increase of 27.63%, showing an N-shaped change of "increase - decrease - increase" on the whole. The ecosystem service value per unit area was more in coastal areas and less in inland areas. From 2005 to 2020, the ecosystem service sensitivity coefficient of the Yellow River Delta wetland was all less than 1. Under the premise of rational development and utilization, it is predicted that the value of ecological services will continue to increase in the future.